LiCl / cellulose nanofiber membrane, preparation method thereof and ionic conductive humidity sensor

The preparation of LiCl/cellulose nanofiber membranes by electrospinning method solves the problem of low sensitivity of existing cellulose humidity sensors under low humidity conditions, and achieves high sensitivity, fast response and long-term stable humidity sensing effect.

CN119571545AActive Publication Date: 2025-03-07TIANJIN UNIV OF SCI & TECH

Patent Information

Application Number
CN202411717996.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-03-07
Estimated Expiration
2044-11-27

AI Technical Summary

Technical Problem

Existing cellulose-based humidity sensors have low sensitivity under low humidity conditions, slow response time, and the sensing performance decreases after high temperature, low temperature and multiple bending cycles.

Method used

LiCl/cellulose nanofiber membrane was prepared by electrospinning method, and cellulose was dissolved through DMAc/LiCl solvent system. DMAc evaporated during electrospinning, and LiCl was retained in cellulose nanofibers, improving the moisture-sensitive detection range and sensitivity of cellulose.

Benefits of technology

It realizes high sensitivity humidity detection under low humidity conditions, has fast response/recovery time, stable performance after long-term use and multiple bending cycles, and a wide detection range of 5%RH to 98%RH.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119571545A_ABST
    Figure CN119571545A_ABST
Patent Text Reader

Abstract

The invention provides a LiCl / cellulose nanofiber composite membrane, a preparation method thereof and an ionic conductive humidity sensor, and belongs to the technical field of biomass nanomaterials. According to the method, cellulose pulp is used as a raw material, cellulose is dissolved in an N, N-dimethylacetamide (DMAc) / lithium chloride (LiCl) solvent system, DMAc is volatilized into air in the electrostatic spinning process, and LiCl is reserved in cellulose nanofibers. In this way, LiCl / cellulose nanofiber films with different LiCl contents can be prepared. The prepared humidity sensor has the advantages of higher sensitivity, wider detection range and short response / recovery time, and can be used in the fields of human respiration monitoring, non-contact humidity testing and the like. The invention provides a new thought for constructing a novel cellulose-based humidity sensor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomass nanomaterials, and in particular relates to a LiCl / cellulose nanofiber membrane and an ion conductive humidity sensor. Background Art

[0002] The detection and management of humidity plays a vital role in human life and the operation of electronic products. The application range of humidity sensors ranges from atmospheric and soil treatment to industrial manufacturing, agricultural production and physiological health management. In addition, water evaporates continuously from the human body due to primary and non-primary sweating. As a biomarker, the ubiquitous human body humidity builds a non-contact human body area sensor network for the emerging wearable digital healthcare. The research on a high-performance non-contact, wearable humidity sensor has attracted widespread attention. Cellulose contains abundant hydrophilic groups on its molecular chain and has good water absorption and swelling properties, so it is considered to be an ideal candidate material for green humidity sensors. Due to the flexibility and versatility of cellulose in material design, cellulose-based sensors can achieve sensing through multiple pathways such as resistance, capacitance, colorimetry, gravity, and microwave. Among them, resistance sensors are considered to be the most promising sensors due to their simple structure, convenient reading and high accuracy. However, since cellulose is not conductive, many conductive materials, including CNTs, PPY, PANI, Ag, RGO, NaCl, KOH, etc., are used to impart compounds with cellulose to improve the conductivity of cellulose, and its conductive mechanism is divided into electronic conductivity and ionic conductivity.

[0003] Traditional cellulose-based humidity sensors are usually designed as two-dimensional materials, such as paper-based humidity sensors and cellulose nanofiber membrane-based humidity sensors. For humidity sensors, wide response range, fast response time and high sensitivity are their key characteristics. Studies have shown that the size and structure of cellulose, as well as its hydrophilic group content, greatly affect the sensing performance of cellulose humidity sensors. In order to improve the sensing performance of cellulose sensors, two strategies can be adopted: one is to nano-size cellulose to expose more hydroxyl groups, and then design the structure of nanofibers. Recent studies have shown that cellulose nanofibers have a large specific surface area and high hydrophilicity, and are therefore more suitable as raw materials for humidity sensors. The patent with publication number CN202410153128.5 provides a cellulose nanofiber membrane and a preparation method thereof, a cellulose nanofiber / carbon nanotube composite membrane and a preparation method thereof, and a humidity sensor. A cellulose nanofiber cellulose membrane is prepared by electrospinning a cellulose spinning solution, which is washed and dried, and carbon nanotubes are filtered on the surface of the cellulose nanofibers as a conductive substance to prepare a cellulose nanofiber / carbon nanotube humidity sensor with a fast response time. The second is to improve the humidity sensitivity of nanofibers by adding hydrophilic substances. Wang et al. published the article "Flexible and Transparent Cellulose-Based Ionic Film as a Humidity Sensor." in the journal ACS Applied Materials & Interfaces (ACS Appl. Mater. Interfaces 2020, 12, 6, 7631–7638), preparing a cellulose / KOH composite ion membrane (CKF) humidity sensor. Since KOH dissolves and ionizes well in water, the resistance of CKF is reduced, so it can produce a fast humidity response.

[0004] Electrospinning technology is one of the fastest-growing methods for preparing nanofibers in recent years. It has the advantages of simple equipment, a wide range of raw materials, and easy control of fiber structure. The prepared nanofibers have a small diameter and a large specific surface area, and the prepared fiber membrane has an adjustable pore size and good pore connectivity. LiCl is a stable ionic compound. As the relative humidity of the air increases, the amount of water adsorbed by LiCl and the number of conductive ions in LiCl also increase, resulting in a decrease in its resistance. When the vapor pressure of LiCl is higher than the partial pressure of water vapor in the air, LiCl releases water, resulting in an increase in its resistance. Therefore, LiCl is considered to be the best electrolytic material for ionic conductive humidity sensors.

[0005] Electrospun nanofibers have the advantages of high specific surface area, large aspect ratio, light weight and easy modification. The diameter of electrospun nanofibers is less than 1 μm, which can greatly expose the hydroxyl groups contained in cellulose nanofibers. However, cellulose-based materials are not conductive due to their structural characteristics. Therefore, combining cellulose and its derivatives with other components including carbon materials and polymers can be used to design high-performance humidity sensors that meet various application requirements, which has become a research hotspot.

[0006] The present invention uses an electrospinning method to prepare an ultrathin LiCl / cellulose nanofiber membrane with a macroporous structure based on cellulose materials. A DMAc / LiCl solvent system is used to dissolve cellulose. During the electrospinning process, DMAc volatilizes into the air and LiCl is retained in the cellulose nanofibers. The LiCl retained in the cellulose has a strong hydrophilicity, which improves the humidity-sensitive detection range of the cellulose nanofibers (especially under low humidity conditions), so that the cellulose humidity sensor has excellent sensitivity (up to 4191%) and a wide detection range (5% to 98% RH). The nanometer size of the cellulose fiber, the extremely low thickness and large pore size of the cellulose membrane accelerate the moisture exchange between the air and the membrane, so that the cellulose humidity sensor has a fast response / recovery time (99 / 110s) and low hysteresis. The performance of the sensor does not decrease after long-term use, high temperature / low temperature conditions and thousands of bending cycles. The humidity sensor is also widely used in the fields of non-contact humidity detection, breathing detection and sleep apnea detection. In addition, based on the experimental results, the mechanism of enhancing the sensor's humidity-sensitive performance through structural optimization was analyzed. Finally, the application potential of the prepared sensor in the actual humidity measurement field was explored, providing new ideas and references for constructing new cellulose-based humidity sensors. Summary of the invention

[0007] In view of this, the object of the present invention is to provide a LiCl / cellulose nanofiber membrane and a preparation method thereof, and an ion conductive humidity sensor. The LiCl / cellulose nanofiber membrane provided by the present invention has excellent moisture absorption capacity and good degradability, and the humidity sensor prepared therefrom has high sensitivity and a wide detection range. The performance of the sensor does not decrease under long-term use, high temperature / low temperature conditions, and thousands of bending cycles.

[0008] In order to achieve the above object, the present invention provides the following technical solutions:

[0009] (1) treating a hardwood pulp board by decomposition and drying to obtain cellulose pulp;

[0010] (2) mixing cellulose pulp with different proportions of DMAc and LiCl to obtain cellulose spinning solutions of different concentrations;

[0011] (3) The cellulose solutions of different concentrations are subjected to electrospinning and then dried to obtain LiCl / cellulose nanofiber membranes with different LiCl contents.

[0012] Preferably, the hardwood pulp in step (1) includes chemical pulp and / or dissolving pulp. The α-cellulose content of the hardwood pulp is 90-99%, the decomposition time is 5-60 minutes, the drying temperature is 50-100° C., and the drying time is 8-15 hours.

[0013] More preferably, the hardwood pulp is dissolving pulp. The hardwood pulp has an α-cellulose content of 95-98%, a disintegration time of 15-30 minutes, a drying temperature of 80-100° C., and a drying time of 10-15 hours.

[0014] Preferably, the mass of the DMAc in step (2) accounts for 80-95% of the total mass of DMAc and LiCl, and the cellulose spinning solutions of different concentrations are 1-10wt%;

[0015] More preferably, the mass of the DMAc in step (2) accounts for 90-95% of the total mass of DMAc and LiCl, and the cellulose spinning solutions of different concentrations are 1-5wt%;

[0016] Preferably, in the preparation process of the LiCl / cellulose nanofiber membranes with different LiCl contents in step (3), the electrospinning conditions include: an applied voltage of 20 to 30 KV, a cellulose spinning solution injection speed of 0.2 to 5 mL / h, a receiving distance of 8 to 25 cm, a collecting device of a hollow receiver, a spinning time of 2 to 10 h, a drying temperature of 100 to 200 ° C after forming, and a drying time of 0.5 to 3 h. The diameter of the LiCl / cellulose nanofibers obtained by the preparation method is 20-800 nm, and the thickness is 18 to 300 μm. The LiCl / cellulose nanofibers are interwoven to form a porous structure with an average pore size of 2 to 10 μm.

[0017] More preferably, in the preparation process of LiCl / cellulose nanofiber membranes with different LiCl contents in step (3), the electrospinning conditions include: an applied voltage of 23 to 28 KV, an injection speed of cellulose spinning solution of 2 to 3 mL / h, a receiving distance of 10 to 20 cm, a drying temperature of 150 to 200° C. after forming, and a drying time of 1 to 3 h.

[0018] The present invention provides a LiCl / cellulose nanofiber composite membrane, comprising a cellulose nanofiber membrane and LiCl loaded on the surface of the cellulose nanofiber membrane; the LiCl / cellulose nanofiber membrane is the LiCl / cellulose nanofiber membrane described in the above scheme or the LiCl / cellulose nanofiber membrane prepared by any preparation method described in the above scheme. The humidity sensor prepared in this way is expected to perform two functions: (1) DMAc / LiCl solvent system is used to dissolve cellulose, DMAc evaporates into the air during electrospinning, and LiCl is retained in the cellulose nanofibers. The LiCl retained on the cellulose has strong hydrophilicity, which improves the humidity detection range of the cellulose nanofibers (especially under low humidity conditions), so that the cellulose humidity sensor has excellent sensitivity (up to 4191%) and a wide detection range (5% to 98% RH). (2) The nanosize of cellulose fibers, the extremely low thickness and large pore size of cellulose membranes accelerate the moisture exchange between air and membranes, so that the cellulose humidity sensor has a fast response / recovery time (99 / 110 s) and low hysteresis. The performance of the sensor does not deteriorate under long-term use, high / low temperature conditions, and thousands of bending cycles, providing new ideas for the construction of new cellulose-based humidity sensors.

[0019] The present invention provides a method for preparing a LiCl / cellulose nanofiber membrane, using cellulose pulp as a raw material. Cellulose is a moisture-sensitive material because a large number of hydroxyl groups in the molecular chain can form hydrogen bonds with water molecules. The principle of the LiCl / cellulose nanofiber composite membrane prepared by the present invention being able to respond to humidity is that under low humidity conditions, the cellulose-based humidity sensor is insensitive to humidity, and when the humidity is <75%, there is no obvious current change, which indicates that under low humidity conditions, although water molecules can be partially ionized in an electrostatic field, no current is formed. However, the LiCl in the cellulose nanofibers can enhance the absorption of water molecules by cellulose, which enables the LiCl / cellulose-based humidity sensor to have a low humidity detection limit of as low as 5%, because LiCl has strong water absorption and can be ionized into Li under low humidity conditions. + and Cl - Ions. Under high humidity conditions, water molecules aggregate into a liquid water layer through physical adsorption, and form more adsorbed water molecule layers in the physical adsorption process according to the Grotthuss chain reaction mechanism. At this time, for cellulose-based humidity sensors, some water molecules are ionized into H+ and OH - , which generates current in the water layer on the surface of cellulose fibers; for LiCl / cellulose-based humidity sensors, H + / OH - LiCl ionization forms Li + / Cl -Under the synergistic effect of the above, the current of the sensor increases significantly due to the intensification of directional migration of ions.

[0020] The advantages of the present invention are: 1. The LiCl retained in the cellulose has a strong hydrophilicity, which increases the humidity detection range of the cellulose fiber (especially under low humidity conditions), thereby giving the cellulose humidity sensor excellent sensitivity. 2. The nanometer size of the cellulose fiber, the extremely low thickness and large pores of the cellulose membrane accelerate the water mass exchange between the air and the membrane, so that the cellulose humidity sensor has a fast response / recovery time. 3. The LiCl / cellulose nanofiber composite membrane prepared by the present invention has a high sensitivity (△I / I0=4190%) and a wide response range of 5%RH to 98%RH; the response / recovery time is 99 / 110s, and the hysteresis is low at 2.9%. In addition, the performance of the humidity sensor will not decrease even after long-term use (>30 days), high temperature / low temperature (73.6 / 0.1°C) and thousands of bending cycles. 4. Compared with traditional multi-walled carbon nanotubes, graphene, polypyrrole and other materials used as humidity responsive materials, the present invention directly uses LiCl in the DMAc / LiCl system of dissolved cellulose as a conductive substance, and prepares a LiCl / cellulose nanofiber composite membrane by electrospinning in one step. LiCl and cellulose nanofibers are used together as humidity responsive materials, which expands the response range of cellulose nanofibers and improves their humidity sensitivity. The cost is lower, the production process is simpler, and the humidity responsive material is more environmentally friendly.

[0021] Humidity sensors have also proven to be suitable for contactless humidity sensing, respiration sensing, and sleep apnea sensing. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.

[0023] Figure 1 SEM images of LiCl / cellulose nanofiber membranes with different LiCl contents (wherein a is the SEM image of Example 1; b is the SEM image of Comparative Example 1; c is the SEM image of Comparative Example 2; d is the SEM image of Comparative Example 3);

[0024] Figure 2The current-voltage curves of LiCl / cellulose nanofiber membrane-based humidity sensors with different LiCl contents (wherein, a is the current-voltage curve of the LCNF08 humidity sensor in Example 2; b is the current-voltage curve of the LCNF07 humidity sensor in Comparative Example 4; c is the current-voltage curve of the LCNF09 humidity sensor in Comparative Example 5; d is the current-voltage curve of the LCNF10 humidity sensor in Comparative Example 6);

[0025] Figure 3 is the humidity sensitivity performance of the LCNF08 humidity sensor (wherein a is the humidity sensitivity curve of LCNF08 in Example 3, and b is the response / recovery time curve of the LCNF08 humidity sensor).

[0026] Figure 4 The preparation process and sensing mechanism of LiCl / cellulose nanofiber composite membrane humidity sensor. DETAILED DESCRIPTION

[0027] The following examples are only for further explanation of the present invention. It should be noted that all technical and scientific terms used in the present invention have the same meanings as in the technical field to which the present invention belongs unless otherwise specified. The experimental methods in the following examples without specifying specific conditions are all based on conventional techniques in the technical field, or according to the conditions recommended by the manufacturer; the reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.

[0028] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, a LiCl / cellulose nanofiber membrane and a preparation method thereof, and an ion conductive humidity sensor provided by the present invention are described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0029] Example 1

[0030] A method for preparing a porous and transparent LiCl / cellulose nanofiber membrane comprises the following steps:

[0031] (1) Preparation of raw materials: Using bleached cellulose pulp as raw material, deflaking and drying it with a deflaking machine to obtain cellulose pulp;

[0032] (2) Dissolution of cellulose: The DMAc / LiCl mass ratio was controlled to be 92:8, DMAc solvent was first added to the cellulose pulp for activation for 2 h, and then LiCl reagent was added to dissolve the cellulose. Finally, the LiCl / cellulose spinning solution was prepared by stirring at room temperature for 8 h, wherein the concentration of the cellulose pulp was 3 wt%, and a LiCl / cellulose solution with a LiCl concentration of 8% was prepared.

[0033] (3) Electrospinning: The LiCl / cellulose solution with a LiCl concentration of 8% was subjected to electrospinning, and a hollow metal receiver was used as a collecting device. The parameters of the electrospinning were: applied voltage 28 kV, flow rate (i.e., cellulose spinning solution injection speed) 2.5 mL / h, receiving distance 15 cm, and spinning time 6 h. After the spinning was completed, the film was peeled off from the collecting net to obtain a LiCl / cellulose nanofiber membrane with a LiCl content of 8%, which was recorded as LCNF08 film according to the LiCl content in the DMAc / LiCl system.

[0034] Comparative Example 1

[0035] The preparation steps were the same as those in Example 1, except that the DMAc / LiCl mass ratio was controlled to be 93:7, and the prepared cellulose film was recorded as LCNF07 film.

[0036] Comparative Example 2

[0037] The preparation steps were the same as those in Example 1, except that the DMAc / LiCl mass ratio was controlled to be 91:9, and the prepared cellulose film was recorded as LCNF09 film.

[0038] Comparative Example 3

[0039] The preparation steps were the same as those in Example 1, except that the DMAc / LiCl mass ratio was controlled to be 90:10, and the prepared cellulose film was recorded as LCNF10 film.

[0040] Example 2

[0041] The LCNF08 film of Example 1 was prepared into a humidity sensor in the following steps:

[0042] The LCNF08 film of Example 1 was used as the humidity sensitive layer, and the film size was cut into 1 cm×2 cm. The LCNF08 film and the copper foil electrodes were connected by conductive silver paste. The copper foil electrodes were respectively connected to the test wires of the digital source meter to prepare the LCNF08 humidity sensor.

[0043] Comparative Example 4

[0044] The LCNF07 film of comparative example 1 was used as the humidity sensitive layer, and the film size was cut into 1 cm×2 cm. The LCNF07 film and the copper foil electrodes were connected by conductive silver paste. The copper foil electrodes were respectively connected to the test wires of the digital source meter to prepare the LCNF07 humidity sensor.

[0045] Comparative Example 5

[0046] The LCNF09 film of comparative example 2 was used as the humidity sensitive layer, and the film size was cut into 1 cm×2 cm. The LCNF09 film and the copper foil electrodes were connected by conductive silver paste. The copper foil electrodes were respectively connected to the test wires of the digital source meter to prepare the LCNF09 humidity sensor.

[0047] Comparative Example 6

[0048] The LCNF10 film of comparative example 3 was used as the humidity sensitive layer, and the film size was cut into 1 cm×2 cm. The LCNF10 film and the copper foil electrodes were connected by conductive silver paste. The copper foil electrodes were respectively connected to the test wires of the digital source meter to prepare the LCNF10 humidity sensor.

[0049] Structure and performance characterization

[0050] 1) The LiCl / fiber membranes prepared in Example 1 and Comparative Examples 1 to 3 were characterized by SEM and pore size analysis was performed.

[0051] Figure 1 The SEM images of LiCl / CNF cellulose membranes with different LiCl contents are shown in Figure 2. Figure 1 a is the SEM image of Example 1; Figure 1 b is the SEM image of Comparative Example 1; Figure 1 Figure c is the SEM image of comparative example 2

[0052] ; Figure 1 d is the SEM picture of Comparative Example 3. Figure 1 As shown, the fibers in Example 1 are uniform and smooth, with an average fiber diameter of 574.72 nm, while the fibers in the cellulose film prepared in Comparative Example 1 are severely interwoven, not smooth, and present obvious beaded shapes, and the fiber distribution is relatively sparse. This is because the low LiCl content in the DMAc / LiCl system causes insufficient dissolution of cellulose, resulting in poor spinning effect.

[0053] like Figure 1 As shown, the fibers in Example 1 are uniform and smooth, with an average fiber diameter of 574.72 nm, while the fibers of the cellulose membrane prepared in Comparative Example 2 are severely bonded and swollen. This is related to the LiCl on the surface of cellulose, which can absorb moisture in the air and cause fiber swelling.

[0054] like Figure 1 As shown, the fibers in Example 1 are uniform and smooth, with an average fiber diameter of 574.72 nm, while the fibers of the cellulose membrane prepared in Comparative Example 3 are more severely bonded and swollen. This is related to the excessively high LiCl content in the DMAc / LiCl system. Excessive LiCl on the cellulose surface can absorb moisture in the air, resulting in severe fiber swelling.

[0055] 2) The humidity sensors of Example 2 and Comparative Examples 4 to 6 were placed in different saturated salt solutions, and the current changes were measured using a digital source meter.

[0056] Figure 2 Current-voltage curves of different LiCl / cellulose nanofiber-based humidity sensors. Figure 2 a is a current-voltage curve diagram of the LCNF08 humidity sensor in Example 2; Figure 2 b is the current-voltage curve of the LCNF07 humidity sensor in Comparative Example 4; Figure 2 Figure c is the current-voltage curve of the LCNF09 humidity sensor in Comparative Example 5; Figure 2 Figure d is the current-voltage curve of the LCNF10 humidity sensor in Comparative Example 6.

[0057] from Figure 2 It can be seen that when the concentration of LiCl is 8%, the current presented is larger (such as Figure 2 When the concentration of LiCl is too low, the cellulose dissolution is not sufficient, resulting in poor film-forming effect of the cellulose membrane, making it difficult to form a uniform and complete conductive network in the LiCl / cellulose composite membrane, and unable to accurately present the change of humidity; when the content of LiCl is too high, due to its strong water absorption capacity, the cellulose nanofibers swell severely, affecting their sensitivity to humidity.

[0058] 3) The humidity sensors of Example 2 and Comparative Examples 4 to 6 were subjected to humidity sensitivity tests.

[0059] The LCNF08 humidity sensor with a LiCl content of 8% used in Example 1 has the best conductivity.

[0060] Figure 3 This is the humidity sensitivity of LCNF08 in Example 2. Figure 3 In the figure, a is the humidity sensitivity curve; b is the response / recovery time curve. Figure 3 As shown, the humidity detection range of the LCNF08 humidity sensor is 5-98%RH. The sensitivity is highest at 98%RH environment, which is 4190%, and the response / recovery time is 99 / 110s.

[0061] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A method for preparing a LiCl / cellulose nanofiber membrane, characterized in that: include: The hardwood pulp board is subjected to deflaking and drying treatment to obtain cellulose pulp; Cellulose pulp was mixed with DMAc and LiCl in different proportions to obtain cellulose spinning solutions with different concentrations; The cellulose solutions with different concentrations are subjected to electrostatic spinning and then dried to obtain LiCl / cellulose nanofiber membranes with different LiCl contents.

2. The preparation method according to claim 1, characterized in that: In the preparation process of the cellulose pulp, the hardwood pulp includes chemical pulp and / or dissolving pulp; the α-cellulose content of the hardwood pulp is 90-99%, the decomposition time is 5-60 minutes, the drying temperature is 50-100° C., and the drying time is 8-15 hours.

3. The preparation method according to claim 1, characterized in that: During the preparation of the cellulose spinning solutions of different concentrations, the mass of the DMAc accounts for 80-95% of the total mass of DMAc and LiCl; and the concentration of cellulose in the cellulose spinning solution is 1-10wt%.

4. The preparation method according to claim 1, characterized in that: In the preparation process of the LiCl / cellulose nanofiber membranes with different LiCl contents, the electrospinning conditions include: an applied voltage of 20 to 30 KV, a cellulose spinning solution injection speed of 0.2 to 5 mL / h, a receiving distance of 8 to 25 cm, a collecting device of a hollow receiver, a spinning time of 2 to 10 hours, a drying temperature of 100 to 200° C. after forming, and a drying time of 0.5 to 3 hours. The diameter of the LiCl / cellulose nanofibers obtained by the preparation method is 20-800 nm, and the thickness is 18 to 300 μm. The LiCl / cellulose nanofibers are interwoven to form a porous structure with an average pore size of 2 to 10 μm.

5. A LiCl / cellulose nanofiber composite membrane, characterized in that: The invention comprises a cellulose nanofiber membrane and LiCl loaded on the surface of the cellulose nanofiber membrane; the cellulose nanofiber membrane is a cellulose nanofiber membrane prepared by the preparation method according to any one of claims 1 to 4.

6. An ion conductive humidity sensor, characterized in that: LiCl and cellulose nanofibers are used together as the moisture-sensitive layer, and a copper sheet is used as the contact electrode, which is connected to a source meter to convert the moisture signal into an electrical signal.

Citation Information

Patent Citations

  • Preparation method of cellulose spinning solution for electrostatic spinning

    CN106929929A

  • Cellulose electrostatic spinning method

    CN107699966A

  • Cellulose / polylactic acid fiber composite paper and preparation method thereof

    CN114481681A

  • Cellulose nanofiber membrane and preparation method thereof, cellulose nanofiber / carbon nanotube composite membrane and preparation method thereof, and humidity sensor

    CN118007322A

  • Multi-response nanocellulose composite membrane and preparation method therefor

    WO2022078032A1

Cited By

  • Preparation method and application of biomass carbon gel material

    CN122441407A